Therapy for acute basilar artery occlusion: a systematic review and meta-analysis [version 1; peer review: 2 approved] - Kevin Sheng; Marcus Tong (F1000Research, 2019)
Purpose: This study aims to analyse the efficacy of different treatment methods for acute basilar artery occlusion, with an emphasis placed on evaluating the latest treatment methods. Method:  A systematic review and meta-analysis was performed to analyse the current data on the therapies available for treating acute basilar artery occlusion. Results: A total of 102 articles were included. The weighted pooled rate of mortality was 43.16% (95% CI 38.35-48.03%) in the intravenous thrombolysis group, 45.56% (95% CI 39.88-51.28) in the intra-arterial thrombolysis group, and 31.40% (95% CI 28.31-34.56%) for the endovascular thrombectomy group. The weighted pooled rate of Modified Ranking Score (mRS) 0-2 at 3 months was 31.40 (95% CI 28.31-34.56%) in the IVT group, 28.29% (95% CI 23.16-33.69%) in the IAT group, and 35.22% (95% CI 32.39-38.09%) for the EVT group. Meta-analyses were also done for the secondary outcomes of recanalization and symptomatic haemorrhage. There was no difference between stent retriever and thrombo-aspiration thrombectomy on subgroup analysis in both clinical outcome and safety profile. Limitations: The included studies were observational in nature. There was significant heterogeneity in some of the outcomes. Conclusions:  Superior outcomes and better recanalization rates for acute basilar occlusion were seen with patients managed with endovascular thrombectomy when compared with either intravenous and/or intraarterial thrombolysis. No superiority of stent‐retrievers over thrombo-aspiration thrombectomy was seen.